(untitled) (Journal of Politics and International Studies, 2024)
This document of research sheds light on the contours of laws concerning the Governance Model of Pakistan. This study explores that most of the laws of the land are either antiquated or irrelevant to the trends and needs of modern governance. Historically, most of these laws of contemporary Pakistan were enacted by the British Parliament in the era of the Pre-Divided Subcontinent. Even the present-day laws of Pakistan are posing obstacles to the modernized governance of the country. Anchored to the tools of Ostrom’s IAD Framework for data collection and data analysis, the researchers have plunged to a finding that Pakistan’s Governance Model, mired by the lacunae of legal contours, has hitherto struggled to attain the desired level of efficiency. Ergo, it is high time there should be a major transformation of the legal system, concerning the Governance Model of Pakistan, enabling it to meet international standards.